ANALISIS PENERAPAN KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK JDU SPAM REGIONAL WOSUSOKAS SEGMEN 3 SUKOHARJO - Giovanni Vivaldi Al Fauzan; Gatot Nursetyo; Herman Susila; Ernie Binti Zulkifli; Nur Shuhada Binti Arbaan; Eko Yuniarsyah (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2026)
Implementation of Occupational Safety and Health (K3) According to the Construction Services Law Number 18 of 1999 that every implementation of construction work must meet the provisions of occupational safety and health. This study aims to determine how much influence the application of OHS has on PT PP - Selaras JO, which is currently under construction in the JDU SPAM Regional WOSUSOKAS Segment 3 Sukoharjo Development Project. This research was conducted by discussing the results of interviews and questionnaires on the contractor team and with the help of SPSS 2024 and Ms Excel. The results of the checklist evaluation of the application of PPE provided by the Company in the Bugel Reservoir Development project with PPE used by workers in the Bugel Reservoir Development project are in accordance but there is still face protection PPE that has not been prepared for concreting and welding work. From the results of research and data processing, it shows that the application of OHS in the JDU SPAM Regional Wosusokas Segment 3 Sukoharjo project is good